2006
DOI: 10.1101/gad.1440206
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Ino80 and Swr1 chromatin remodeling enzymes regulates cell cycle checkpoint adaptationin response to DNA damage

Abstract: Supplemental material is available at http://www.genesdev.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
170
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(181 citation statements)
references
References 46 publications
(85 reference statements)
10
170
1
Order By: Relevance
“…yINO80 has also been shown to induce γ-H2AX following exposure to DNA-damaging agents and to modulate downstream DNA damage checkpoint functions [26,58]. We found that both γ-H2AX and 53BP1 efficiently localized to IR-induced DSBs and to dysfunctional telomeres in mIno80 ∆/∆ MEFs, suggesting that mIno80 is not required for the accumulation of γ-H2AX and 53BP1 at DNA damage sites.…”
Section: Discussionmentioning
confidence: 74%
“…yINO80 has also been shown to induce γ-H2AX following exposure to DNA-damaging agents and to modulate downstream DNA damage checkpoint functions [26,58]. We found that both γ-H2AX and 53BP1 efficiently localized to IR-induced DSBs and to dysfunctional telomeres in mIno80 ∆/∆ MEFs, suggesting that mIno80 is not required for the accumulation of γ-H2AX and 53BP1 at DNA damage sites.…”
Section: Discussionmentioning
confidence: 74%
“…Perhaps the most specialized function of remodelers involves histone-variant exchange. Only SWR1 efficiently replaces H2A-H2B dimers with Htz1-H2B dimers in vitro 19 , and new in vivo evidence supports a role for the INO80 remodeler in the reverse reaction, which may be important for recovery from DNA repair 26 .…”
mentioning
confidence: 86%
“…A possible other substrate of Cdc5 in the adaptation response is the Ino80 chromatin remodeling complex (Papamichos-Chronakis et al 2006). Loss of Ino80 activity in yeast cells cause aberrant incorporation of histone H2AZ variant in chromatin proximal to DSBs and is associated with an inability to adapt to DNA damage.…”
Section: Polo-like Kinasesmentioning
confidence: 99%
“…It is believed that Ino80 acts by maintaining high levels of phosphorylated histone H2AX in damaged cells. In the absence of Ino80 complex, another chromatin remodeling factor replaces phospho-H2AX with H2AZ, thereby limiting checkpoint activation (Papamichos-Chronakis et al 2006). It will be interesting to determine whether Ino80 complex components are substrates for Cdc5 during the cell cycle or in response to DNA damage.…”
Section: Polo-like Kinasesmentioning
confidence: 99%